In vitro and in vivo evaluation of a magnetic resonance imaging-guided focused ultrasound system for dissolving clots in combination with thrombolytic drugs - Damianou, Christakis A.; Hadjisavvas, Venediktos; Ioannides, Kleanthis (My University, 2014)
Background The potential of a magnetic resonance imaging (MRI)-guided focused ultrasound (MRgFUS) system combined with thrombolytic drugs to dissolve clots is investigated using in vitro and in vivo models. Methods Two spherically focused transducers of 5 cm diameter focusing at 10 cm and operating at either.5 or 1 MHz were used. Doppler ultrasound was used to measure the blood flow during the in vivo experiments. Results The effect of ultrasound intensity, transducer beam area, and frequency on the dissolved volume was investigated. The goal was to maintain a temperature increase of less than 1°C (called safe temperature) at the clot during the application of pulsed ultrasound and at the same time achieve efficient thrombolysis. Conclusions The MRgFUS technique was proven successful in dissolving clots in vitro and in vivo. It was found that the volume of dissolved clot increases with acoustic intensity and beam size and decreases with frequency. With this system, it was possible to push ultrasound through a plastic phantom skull using a.5 MHz transducer. The beam of ultrasound through the phantom skull was monitored using the MRI technique of fast spoiled gradient. Finally, the thrombus in the in vivo model (ear artery) was successfully destroyed with the therapeutic protocols investigated in the in vitro models. This study shows that FUS using a single element MR-compatible transducer has the potential to treat clots in synergy with thrombolytic drugs. More advanced MRgFUS systems, such as phased arrays, will have a greater impact in sonothrombolysis.
Keywords: MRI; Robot; Stroke; Thrombolysis